Racial residential segregation, neighborhood disorder, and racial discrimination among black pregnant women. Issue 5 (3rd March 2022) - Dove‐Medows, Emily; Misra, Dawn P.; McCracken, Lindsey; Giurgescu, Carmen
Abstract: Objective: To compare and contrast pregnant, Black women's voices with quantitative measures of racial residential segregation, neighborhood disorder, and racial discrimination. Design and sample: Using a convergent design for the parent study, surveys and qualitative interviews were completed by Black pregnant women ( n = 27). Measures: Content analysis was conducted and data were analyzed to assess for congruency or divergence for each concept related to structural racism (racial residential segregation, neighborhood disorder, and discrimination). Results: No single concept had 100% agreement across qualitative and quantitative approaches. Participants disclosed experiences during some interviews that were not captured by the surveys. The qualitative interviews offered a more detailed description of the concepts which along with the quantitative measures, provided insights about how participants perceived these mechanisms. Discussion: While important relationships about the mechanisms of structural racism and preterm birth can be examined using a single approach, using mixed methods can offer more insights about how those most impacted by preterm birth relate to these mechanisms. Future work will best add to the understanding of structural racism and preterm birth when study measures accurately reflect the experiences of the people who experience racism.